The Intersession Process in Psychotherapy for Anorexia Nervosa: Characteristics and Relation to Outcome. Issue 9 (16th May 2016) - Hartmann, Armin; Zeeck, Almut; Herzog, Wolfgang; Wild, Beate; de Zwaan, Martina; Herpertz, Stephan; Burgmer, Markus; von Wietersheim, Joern; Tagay, Sefik; Dinkel, Andreas; Löwe, Bernd; Resmark, Gaby; et al.
Abstract : Objective: The "inter session process" (ISP) is defined as therapy‐related conscious thoughts, memories, and emotions that patients and therapists experience between psychotherapy sessions. It indicates how the participants process and use treatment. The main aim of this study is to describe the ISP characteristics of patients in outpatient treatment for anorexia nervosa (AN). An additional aim is to explore the relation between patients' ISP and treatment outcome. Method: Patients taking part in a randomized controlled trial on outpatient psychotherapy for AN (ANTOP) filled in the Intersession Experience Questionnaire before each of the 40 psychotherapy sessions. Trajectories of different aspects of the ISP were analyzed with growth curve models based on orthogonal polynomials and tested for differences between 3 outcome categories (recovery, partially recovered, full syndrome AN). Results: Data from 108 cases were available for analysis. ISP facets showed diverse, mostly nonlinear, trajectories over the course of treatment. Less favorable outcomes were associated with higher levels of patients' experiencing negative emotions when recalling therapeutic dialogue, thinking about therapy during dreaming/drowsy states, and applying therapeutic learning (in the second half of treatment). Conclusions: Findings confirm an overall relation between ISP and treatment outcome. In outpatient treatment in AN, patients with a less successful course seem to be more preoccupied with therapy and therapist between sessions. For the ISP facet "applying therapeutic learning, " findings point to an optimal range dependent on treatment phase. Growth curve modeling is required to describe the nonlinear trajectories of ISP facets.